2013
DOI: 10.5152/jtgga.2013.55452
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mean platelet volume, neutrophil/lymphocyte ratio and platelet/lymphocyte ratio in advanced stage endometriosis with endometrioma

Abstract: Objective:We compared the preoperative values of mean platelet volume (MPV) and peripheral systemic inflammatory response (SIR) markers (neutrophil/lymphocyte ratio and platelet/lymphocyte ratio) between patients with advanced-stage (stage 3/4) endometriosis having endometrioma (OMA) and patients with a non-neoplastic adnexal mass other than endometrioma (non-OMA). Material and Methods:Patients who underwent operations with the pre-diagnosis of infertility or adnexal mass and who underwent laparoscopic tubal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 31 publications
6
49
1
1
Order By: Relevance
“…Similar to the present results, no significantly different levels of MPV were reported in patients of hemodialysis, renal transplanted, peritoneal dialysis and chronic renal failure patients when compared to each other 34 as well as in patients with advanced stage endometriosis. 35 Accordingly to the reported studies about colon and non-small cell lung cancers, 22,23 PLR was found to be significantly higher in patients with moderate to severe disease activity when compared to patients with mild disease activity and healthy controls and it had a weakly but significant correlation with BASDAI scores in the present study. Albeit, the level of inflammation in advanced stage endometriosis that is proven to develop with severe inflammation was shown to have no significant association with PLR.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar to the present results, no significantly different levels of MPV were reported in patients of hemodialysis, renal transplanted, peritoneal dialysis and chronic renal failure patients when compared to each other 34 as well as in patients with advanced stage endometriosis. 35 Accordingly to the reported studies about colon and non-small cell lung cancers, 22,23 PLR was found to be significantly higher in patients with moderate to severe disease activity when compared to patients with mild disease activity and healthy controls and it had a weakly but significant correlation with BASDAI scores in the present study. Albeit, the level of inflammation in advanced stage endometriosis that is proven to develop with severe inflammation was shown to have no significant association with PLR.…”
Section: Discussionsupporting
confidence: 77%
“…Albeit, the level of inflammation in advanced stage endometriosis that is proven to develop with severe inflammation was shown to have no significant association with PLR. 35 Nevertheless, these results also may indicate that PLR reflects disease activity in AS.…”
Section: Discussionmentioning
confidence: 88%
“…Role of basophil and eosinophil still contradiction. In this study showed response of the basophil and eosinophil was not different in infected endometrioma and endometrioma [10,15,16,20,21].…”
Section: Discussionmentioning
confidence: 55%
“…But in this study NLR in infected endometrioma 11.04+9.63 showed correspond to the previous study. This is because the neutrophil act as innate immunity and suppressed the lymphocyte as a response to the bacteria [8,9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation